Distribution of extraintestinal pathogenic Escherichia coli O-serotypes and antibiotic resistance in blood isolates collected from patients in a surveillance study in Japan. Issue 11 (November 2022) - Matsumoto, Tetsuya; Mikamo, Hiroshige; Ohge, Hiroki; Yanagihara, Katsunori; Weerdenburg, Eveline; Go, Oscar; Spiessens, Bart; van Geet, Gunter; van den Hoven, Thijs; Momose, Atsushi; Hagiwara, Yosuke; Nakayama, Yoshikazu; et al.
Abstract: Introduction: Invasive extraintestinal pathogenic Escherichia coli (ExPEC) disease (IED), characterised by sepsis and bacteraemia, is a major global healthcare concern worsened by emerging multidrug resistant (MDR) strains. The development of multivalent prophylactic vaccines targeting E. coli strains of IED-associated O-serotypes could address this. A better understanding of O-serotype distribution is required for this purpose. Here, we characterised O-serotype prevalence and drug resistance among ExPEC bacteraemia isolates in Japan. Methods: E. coli blood isolates from patients aged ≥60 years with bacteraemia were obtained from a retrospective surveillance study in Japan (2015–2017). O-serotyping was performed by agglutination; for isolates non-typeable by agglutination, O-genotyping was performed. Antimicrobial susceptibility was evaluated by broth microdilution using a 21-antibiotic panel. The frequency of drug resistant (DR) isolates was evaluated by antimicrobial susceptibility testing. Results: Of 401 ExPEC bacteraemia isolates evaluated, the most prevalent O-serotype (≥1%) was O25 (28.7% [n = 115]), followed by O1 (14.2% [n = 57]), O2 (8.5% n = 34]), O6 (5.5% [n = 22]), O75, O18, O13, O16, O15, O4, O46/O134, O86, O8 and O83 (each <5% prevalence). These 14 O-serotypes accounted for 81.5% of isolates collected. In total, 19% (n = 77) of isolates were DR ≥ 3, of which 59.7% were O25. Fluoroquinolone-resistance among all and O25 isolates was most prevalent (35.7% and 84.3%, respectively). Almost all (98%) isolates identified as O25 were of subtype O25B. Conclusions: E. coli serotype O25B showed the highest prevalence and highest multidrug resistance among ExPEC bacteraemia isolates from patients ≥60 years in Japan. Our data may inform development of multivalent glycoconjugate vaccines to prevent IED.